The collapse of cooperation: the endogeneity of institutional break-up and its asymmetry with emergence - Cordes, Christian; Elsner, Wolfram; Graebner, Claudius; Heinrich, Torsten; Henkel, Joshua; Schwardt, Henning; Schwesinger, Georg; Su, Tong-Yaa (Journal of evolutionary economics, 2021)
Decline and break-up of institutionalized cooperation, at all levels, has occurred frequently. Some of its concomitants, such as international migration, have become topical in the globalized world. Aspects of the phenomenon have also become known as failing states. However, the focus in most social sciences has been on institutional emergence and persistence, not collapse. We develop an endogenous explanation of collapsing institutions. Collapse may be an implication of the very economic success of institutionalized cooperation and of increasing system complexity, when cognitive conditions for effective collective decision-making do not proportionately evolve. Moreover, we show that collapse is not a simple logical reverse of emergence. Rather, institutions break up at different factor constellations than the ones prevailing at emergence. We approach endogenous institutional break-up and its asymmetry from various paradigmatic and disciplinary perspectives, employing psychology, anthropology, network analysis, and institutional economics. These perspectives cover individuals, groups, interaction-arenas, populations, and social networks.
Gesehen am 25.10.2021
Keywords: Aufsatz in Zeitschrift